Answer:
5) The equation of the straight line is 2 x - y + 1 =0
6) The equation of the straight line is x + y -5 =0
7) The equation of the straight line is 5 x + 6 y - 24 =0
8) The equation of the straight line is x - 4 y -4 =0
9) The equation of the parallel line is 3x + y -19 =0
Step-by-step explanation:
5)
The equation of the straight line is
![y - y_{1} = m ( x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%20%3D%20m%20%28%20x%20-%20x_%7B1%7D%20%29)
Slope of the line
![m = \frac{y_{2}-y_{1} }{x_{2}-x_{1} }](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_%7B2%7D-y_%7B1%7D%20%20%7D%7Bx_%7B2%7D-x_%7B1%7D%20%20%7D)
Given points are (1,3) , ( -3,-5)
![m = \frac{-5-3 }{-3-1 } = \frac{-8}{-4} = 2](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-5-3%20%20%7D%7B-3-1%20%7D%20%3D%20%5Cfrac%7B-8%7D%7B-4%7D%20%3D%202)
The equation of the straight line is
![y - y_{1} = m ( x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%20%3D%20m%20%28%20x%20-%20x_%7B1%7D%20%29)
![y - 3 = 2 ( x - 1 )](https://tex.z-dn.net/?f=y%20-%203%20%3D%202%20%28%20x%20-%201%20%29)
y = 2x - 2 +3
2 x - y + 1 =0
The equation of the straight line is 2 x - y + 1 =0
6)
The equation of the straight line is
![y - y_{1} = m ( x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%20%3D%20m%20%28%20x%20-%20x_%7B1%7D%20%29)
Slope of the line
![m = \frac{y_{2}-y_{1} }{x_{2}-x_{1} }](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_%7B2%7D-y_%7B1%7D%20%20%7D%7Bx_%7B2%7D-x_%7B1%7D%20%20%7D)
Given points are (1,4) , ( 6,-1)
![m = \frac{-1-(4) }{6-1 } = \frac{-5}{5} = -1](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-1-%284%29%20%20%7D%7B6-1%20%7D%20%3D%20%5Cfrac%7B-5%7D%7B5%7D%20%3D%20-1)
The equation of the straight line is
![y - y_{1} = m ( x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%20%3D%20m%20%28%20x%20-%20x_%7B1%7D%20%29)
![y - 1 = -1 ( x - 4 )](https://tex.z-dn.net/?f=y%20-%201%20%3D%20-1%20%28%20x%20-%204%20%29)
y - 1 = - x +4
The equation of the straight line is x + y -5 =0
7)
The equation of the straight line is
![y - y_{1} = m ( x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%20%3D%20m%20%28%20x%20-%20x_%7B1%7D%20%29)
Slope of the line
![m = \frac{y_{2}-y_{1} }{x_{2}-x_{1} }](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_%7B2%7D-y_%7B1%7D%20%20%7D%7Bx_%7B2%7D-x_%7B1%7D%20%20%7D)
Given points are (-12 , 14) , ( 6,-1)
![m = \frac{-1-(14) }{6+12 } = \frac{-15}{18} = \frac{-5}{6}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-1-%2814%29%20%20%7D%7B6%2B12%20%7D%20%3D%20%5Cfrac%7B-15%7D%7B18%7D%20%3D%20%5Cfrac%7B-5%7D%7B6%7D)
![y - 14 = \frac{-5}{6} ( x - (-12) )](https://tex.z-dn.net/?f=y%20-%2014%20%20%3D%20%5Cfrac%7B-5%7D%7B6%7D%20%20%28%20x%20-%20%28-12%29%20%29)
6( y - 14 ) = - 5 ( x +12 )
6 y - 84 = - 5x -60
5 x + 6 y -84 + 60 =0
5 x + 6 y - 24 =0
8)
The equation of the straight line is
![y - y_{1} = m ( x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%20%3D%20m%20%28%20x%20-%20x_%7B1%7D%20%29)
Slope of the line
![m = \frac{y_{2}-y_{1} }{x_{2}-x_{1} }](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_%7B2%7D-y_%7B1%7D%20%20%7D%7Bx_%7B2%7D-x_%7B1%7D%20%20%7D)
Given points are (-4 , -2) , ( 4 , 0)
![m = \frac{0+2}{4 +4} = \frac{2}{8} = \frac{1}{4}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B0%2B2%7D%7B4%20%2B4%7D%20%20%3D%20%5Cfrac%7B2%7D%7B8%7D%20%3D%20%5Cfrac%7B1%7D%7B4%7D)
![y - (-2) =\frac{1}{4} ( x - (-4) )](https://tex.z-dn.net/?f=y%20-%20%28-2%29%20%20%3D%5Cfrac%7B1%7D%7B4%7D%20%28%20x%20-%20%28-4%29%20%29)
4 ( y + 2) = x + 4
x - 4 y -4 =0
9)
The equation of the line y = 3x + 6 is parallel to the line
3x + y + k =0 is passes through the point ( 4,7 )
⇒ 3x + y + k =0
⇒ 12 + 7 + k =0
⇒ k = -19
The equation of the parallel line is 3x + y -19 =0